2017
DOI: 10.1108/jstpm-09-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Relation between start-ups’ online social media presence and fundraising

Abstract: The emergence of social media such as Facebook and Twitter have changed the way human beings communicate and interact in the context of business settings. In order to further explore the use of social media for entrepreneurs, we have explored how entrepreneurs use social media for fund-raising purposes. The novelty of this study is the use of social relationships (represented by social network features) as the main way to predict whether or not funding investments will occur. We use Application Programming Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 62 publications
(103 reference statements)
0
31
0
Order By: Relevance
“…Moreover, they find a quadratic relationship between the number of Twitter posts and funds raised, such that more posts initially increase funding while too many posts harm the outcome. In a similar vein, Yang and Berger (2017) have recently shown a positive relationship between the number of followers and the amount of startup funding. Likewise, Nevin et al (2017) show that the number of social media posts has a positive effect on funds raised through crowdfunding.…”
Section: Startup Financingmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, they find a quadratic relationship between the number of Twitter posts and funds raised, such that more posts initially increase funding while too many posts harm the outcome. In a similar vein, Yang and Berger (2017) have recently shown a positive relationship between the number of followers and the amount of startup funding. Likewise, Nevin et al (2017) show that the number of social media posts has a positive effect on funds raised through crowdfunding.…”
Section: Startup Financingmentioning
confidence: 84%
“…Based on existing research in crowdfunding and venture capital, we posit that social media activity, as proxied by the number of followers and the number of postings, will positively influence funds raised at ICOs. At least two transmission mechanisms for this expected effect come to mind (Jin et al 2017;Yang and Berger 2017): First, social media activity may serve as a marketing channel for announcing ICOs and distributing information about the underlying new tokens. Thus, in line with the "salience view" (Solomon et al 2012), increased social media activity will lead to increased salience of an ICO, directing potential investors to the upcoming investment opportunity (Sprenger et al 2014).…”
Section: Startup Financingmentioning
confidence: 99%
“…Moreover, they find a quadratic relationship between the number of Twitter posts and funds raised, such that more posts initially increase funding while too many posts harm the outcome. In a similar vein, Yang and Berger (2017) have recently shown a positive relationship between the number of followers and the amount of startup funding. Likewise, Nevin et al (2017) show that the number of social media posts has a positive effect on funds raised through crowdfunding.…”
Section: Startup Financingmentioning
confidence: 84%
“…Based on existing research in crowdfunding and venture capital, we posit that social media activity as proxied by the number of followers and the number of postings will positively influence funds raised at ICOs. At least two transmission mechanisms for this expected effect come to mind (Jin et al, 2017;Yang & Berger, 2017): First, social media activity may serve as a marketing channel for announcing ICOs and distributing information about the underlying new tokens. Thus, in line with the "salience view" (Solomon et al, 2012), increased social media activity will lead to increased salience of an ICO, directing potential investors to the upcoming investment opportunity (Sprenger et al, 2014).…”
Section: Startup Financingmentioning
confidence: 99%
“…In result, previous studies show that the emergence of online networking has opened the door for innovative companies to connect with each other and to operate more efficiently [15]. One way to understand how start-ups can increase their chances of receiving funding investment from investors is to understand one's business networking behavior [34]. For example, Agrawal et al (2011) suggested that understanding both the mechanisms of crowdfunding and how to reach networks is the key to crowdfunding success.…”
Section: Networkingmentioning
confidence: 99%